Grundvorstellungen zu Bruchzahlen – auch für leistungsschwache Schüler? Eine mehrperspektivische Interviewstudie zu Lösungsprozessen, Emotionen und Beliefs in der Hauptschule (mathematica didactica, 2006)
Can low achievers in secondary schools solve tasks which aim on the development of basic ideas (‚Grundvorstellungen‘) for fractions? And are these tasks helpful for them? To answer these questions a multi perspective interview study focusing on students’solving processes, emotions and beliefs was led through. From the results there can be drawn conclusions for the development of open tasks for low achievers, especially for the development of tasks which submit the learning of the concept of fractions.